1985
DOI: 10.1093/carcin/6.6.847
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of nitrate in humans: role of gastrointestinal absorption and metabolism

Abstract: A model to describe the response of the blood pool to an oral dose of nitrate in humans has been developed. The permeability-area product of the small intestine to nitrate was estimated by comparing simulations from a three-compartment model with published data for blood nitrate concentration following nitrate ingestion. The transport of nitrate from the bloodstream to the lumen of the large intestine and the metabolism of nitrate by enteric bacteria were examined by including an additional compartment represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The average daily intake of NO 3 Ϫ is estimated to be about 40-50 mg/d for adults, based on studies in Denmark and the United Kingdom (1)(2)(3). Typical serum levels in the Western world range from 10-140 mol/L with a mean of 30-50 mol/L (3)(4)(5)(6)(7)(8)(9), and the serum half life is 5-8 hours (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The average daily intake of NO 3 Ϫ is estimated to be about 40-50 mg/d for adults, based on studies in Denmark and the United Kingdom (1)(2)(3). Typical serum levels in the Western world range from 10-140 mol/L with a mean of 30-50 mol/L (3)(4)(5)(6)(7)(8)(9), and the serum half life is 5-8 hours (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of nitrate to nitrite in vivo may be effected by both enteric bacteria and mammalian nitrate reductase activity. Many species of micro-organisms resident in the orogastrointestinal tract possess nitrate reductase activity [24], and this enzyme has been detected in rat liver and intestinal mucosa, although at much lower activity [23]. From comparative studies in germ-free and conventional rats in our laboratory, we concluded that of the 40-50% of a dose of nitrate reduced to nitrite in conventional animals approximately half was effected by mammalian nitrate reductase [25].…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 85%
“…The excretion follows first-order kinetics, and the elimination half-life has been estimated to be about 5 h [21]. Some metabolic conversion of nitrate clearly occurs (see Figure l), since in humans about 3% of a dose of "NO; appeared in urine as urea and ammonia [22]; in rats 11% of the dose appeared as urea and ammonia in urine and faeces [23].…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%
“…However, these species are highly susceptible to oral nitrite intake (for example, in mouldy hay) because they cannot convert from nitrite to ammonia (Yaremcio, 1991). The significant role of alimentary tract micro-organisms in the metabolism of nitrate has been demonstrated in experiments with germ-free (monogastric) rats which excreted in urine approximately 20 % more nitrate than conventional rats (Schultz et al, 1985).…”
Section: Metabolismmentioning
confidence: 99%